2014
DOI: 10.1103/physrevx.4.041049
|View full text |Cite
|
Sign up to set email alerts
|

Model Realization and Numerical Studies of a Three-Dimensional Bosonic Topological Insulator and Symmetry-Enriched Topological Phases

Abstract: We study a topological phase of interacting bosons in (3 þ 1) dimensions that is protected by charge conservation and time-reversal symmetry. We present an explicit lattice model that realizes this phase and that can be studied in sign-free Monte Carlo simulations. The idea behind our model is to bind bosons to topological defects called hedgehogs. We determine the phase diagram of the model and identify a phase where such bound states are proliferated. In this phase, we observe a Witten effect in the bulk whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
(181 reference statements)
1
18
0
Order By: Relevance
“…In both cases we recovered topological orders in agreement with previous works that treated isotropic systems with local time-reversal symmetry [17,55,56]. Given these successes it is natural to ask when a symmetric surface can be reliably distilled to a quasi-1D setup with reduced symmetry while preserving the structure of possible surface phases.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In both cases we recovered topological orders in agreement with previous works that treated isotropic systems with local time-reversal symmetry [17,55,56]. Given these successes it is natural to ask when a symmetric surface can be reliably distilled to a quasi-1D setup with reduced symmetry while preserving the structure of possible surface phases.…”
Section: Discussionsupporting
confidence: 85%
“…A rich story is now emerging [58]. Previous work has demonstrated that interactions allow one to (i) smoothly connect certain phases that are topologically distinct in the free-particle limit [33,[59][60][61][62][63][64][65][66][67], (ii) generate new shortrange-entangled topological phases with no noninteracting counterpart, for both bosonic and fermionic systems [17,68,69], and (iii) form gapped topological orders at the boundary of a 3D topological phase that cannot exist in strictly 2D systems with the same symmetry [13][14][15][16][17]55,56,[65][66][67]70,71]. To this list we have added a new possibility: Strong interactions can nucleate exotic gapless composite Dirac liquids at the surface of a 3D electronic TI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, with interactions, several groups [23][24][25][26] described how a symmetry preserving gapped surface can emerge for the bulk topological insulator. Inspired by similar constructions [27][28][29][30][31] for bosonic analogs of the topological insulators these papers showed that such a symmetry preserving gapped surface requires the kind of topological order familiar from discussions of the fractional quantum Hall effect and some quantum spin liquids. However, the symmetry is implemented in this topologically ordered state in a manner that is forbidden ("anomalous") in a strictly two-dimensional system.…”
Section: B Interacting Topological Insulators In Three Dimensionsmentioning
confidence: 99%
“…Two dimensional systems are a natural playground for fractional statistics, since they provide a classification of trajectories of point particles in terms of winding numbers. However, the expansion of the world of topological systems from two to three dimensions, which was initiated by the discovery of the 3D topological insulators, naturally suggests a search for 3D fractional topological insulators 32,[58][59][60][61][62][63][64] . Defining characteristics of such a phase may be expected to be a degeneracy of the ground state on the boundary-less three dimensional torus, a surface quantum Hall effect of ν = (pe 2 )/2qh (with p/q being a fraction), fractionally charged excitations in the bulk, mutual statistics between bulk point and loop particles and a coupling of fractional charges to monopoles in the bulk.…”
Section: Three Dimensional Fractional Topological Insulatorsmentioning
confidence: 99%